Inhibition of steel corrosion by calcium benzoate adsorption in nitrate solutions: Theoretical and experimental approaches - Blustein, Guillermo (2004)
The inhibitive effects of calcium benzoate on steel corrosion were studied in sodium nitrate solutions at room temperature. Corrosion parameters of the steel/nitrate and steel/benzoate+nitrate interfaces were obtained from polarization curves. Adsorption parameters of benzoate on steel in sodium nitrate solutions were determined through changes in the degree of surface coverage by the inhibitor, as a function of concentration, time, and adsorption potential. The most likely adsorption configuration of benzoate on iron was envisaged with the help of semiempirical calculations such as extended Hückel calculations. A two-dimensional flat configuration was involving at least two metal atoms, one interacting with the phenolic group and the other with the carboxylate moiety. The effect of chloride on the corrosion inhibition of benzoate was analyzed by exposing the metal to different chloride solution concentrations, from which corrosion parameters were calculated and compared with those in nitrate solutions.